Current approaches to management of bone sarcoma in adolescent and young adult patients. Issue 2 (12th November 2021) - Ingley, Katrina M.; Maleddu, Alessandra; Grange, Franel Le; Gerrand, Craig; Bleyer, Archie; Yasmin, Ephia; Whelan, Jeremy; Strauss, Sandra J.
Abstract: Bone tumors are a group of histologically diverse diseases that occur across all ages. Two of the commonest, osteosarcoma (OS) and Ewing sarcoma (ES), are regarded as characteristic adolescent and young adult (AYA) cancers with an incidence peak in AYAs. They are curable for some but associated with unacceptably high rates of treatment failure and morbidity. The introduction of effective new therapeutics for bone sarcomas is slow, and to date, complex biology has been insufficiently characterized to allow more rapid therapeutic exploitation. This review focuses on current standards of care, recent advances that have or may soon change that standard of care and challenges to the expert clinical research community that we suggest must be met.